Electrocoagulation: an electrochemical process for water clarification - Éva Fekete; Béla Lengyel; Tamás Cserfalvi; Tamás Pajkossy (Journal of Electrochemical Science and Engineering, 2016)
Electrocoagulation is a group of various procedures used for removing contaminants from water by electrochemically dissolving aluminum or iron. The contaminants of the solution may be incorporated in the in situ forming metal hydroxide flocs, which can be filtered as a precipitate or skimmed as a float. The main features of the procedure are highlighted on the example of cleaning of an oily waste-water. Design parameters of a 1 m3/h waste-water cleaning system are calculated from the results of small-scale experiments.